On the Performance of Civil Servants at Marine and Fishery Service Office Majene District - Nur Qamariah S; Awal Nopriyanto Bahasoan; Zulkarnaen Hadi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The aim of this research is to determine the effect of job training and motivation on civil servant performance at the Marine and Fisheries Service Office of Majene Regency. By using the SPSS method, there were 31 respondents who were used as samples in this study, namely employees of the Department of Marine Affairs and Fisheries of Majene Regency. The type of data used in this study is primary data. Data collection techniques were carried out by distributing questionnaires to the research sample. T-test analysis is used to test in this study. The results of this study indicate that job training has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, job training and motivation together, has a positive and significant effect on employee performance at the Marine and Fisheries Office of Majene Regency.